Odpowiedzi

2009-09-03T22:30:55+02:00
1,(41)

1 całą omijamy (dodamy na końcu przykładu)

0,(41) = x | *100
41,(41) = 100x | -x
41 = 99x | /99
41/99 = x

1,(41) = 1 i 44/99



0,2(1) = 0,2 + 0,0(1)

x = 0,0(1) |*10
10x = 0,1(1) |-x
9x = 0,1 | /9
x = 1/90

0,2(1) = 1/5 + 1/90 = 19/90


3,1(4) = 3 + 0,1 + 0,0(4)

0,0(4) = x |*10
0,4(4) = 10x |-x
0,4 = 9x
x = 2/45

3,1(4) = 3 + 1/10 + 2/45 = 3 i 13/90

27,0(51) = 27 + 0,0(51)

0,0(51) = x | *100
5,1(51) = 100x |-x
5,1 = 99x
x = 17/330

27,0(51) = 27 i 17/330